Corrosion of Cu-doped Ni–Mo low-alloy steel in a severe marine environment. (April 2022) - Zhang, Tianyi; Liu, Wei; Dong, Baojun; Mao, Rui; Sun, Yipu; Chen, Longjun
Abstract: The corrosion performance of Cu-doped Ni–Mo steel has been comprehensively studied in a simulated severe marine environment. Results have indicated that the addition of Cu accelerates the generation of corrosion products and increases the corrosion current density during the initial corrosion process, which can be attributed to the increased proportion of high-angle grain boundaries. Cu improves the long-term protection of a rust layer by forming CuFeO2, and stabilizes substances such as NiFe2 O4 and compounds containing Mo 4+ and Mo 6+ . Rust layers optimized by Cu display improved electrochemical properties in 3.5 wt% NaCl solution, indicating the beneficial effect of Cu on their protective properties. Highlights: The effects of Cu on the corrosion of Ni–Mo steel have been comprehensively characterized. The proportion of high-angle grain boundaries (HAGBs) is increased by the addition of Cu, leading to increased electrochemical activity of Ni–Mo steel during the initial corrosion process. The protective effect of a rust layer is increased by the generation of CuFeO2, which stabilizes NiFe2 O4 and compounds containing Mo 4+ and Mo 6+ .